Populism in the political culture of Turkey: The foreign policy dimension - P. V. Shlykov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper analyses the phenomenon of populism and its impact on Turkish foreign policy in three dimensions: institutional, instrumental and ideological. The research scrutinizes a wide selection of party manifestos and public speeches of Turkish politicians with primarily focus on Recep Tayyip Erdoğan’s statements during his incumbency as the prime-minister and the president. The embeddedness of populism in political culture of Turkey provided it with ideological ﬂexibility and made populism almost a universal instrument for engaging with electorate. Starting from Turkey’s transition to multiparty system the majority of political actors have resorted to populism in one or another way. Erdoğan has not only continued this tendency but mastered the populist rhetoric. The character and content of Erdoğan’s populism ﬂuctuated following the changing domestic and international environment. In the 2000s it was hinged on the loose concept of conservative democracy. At the turn of the 2000s and 2010s the dreams for the EU membership gave way to ideas of ‘civilizational expansionism’ which had the concept of Islamic/Ottoman civilization as its core. From the mid-2010s ultra nationalism has come to the forefront of the populist rhetoric. Eventually, the populist binary opposition of ‘us’ and ‘they’ took a deﬁnite shape of global confrontation between Turkey as a defender of Islam and the ‘adverse’ West. Populist rhetoric helped Erdoğan to justify his almost two-decades-long incumbency and evade direct responsibility for economic hardships of the 2010s. Populism has become an eﬀective instrument to monopolize the foreign policy in the hands of Erdoğan. Utilizing negative rhetoric against Turkish professional diplomats within the last decade Erdoğan has managed to cement his clout over the foreign-policy making. Institutionally the expansion of populism in the sphere of foreign policy led to its ‘domestication’ and ‘nationalization’ while its impact on the foreign policy discourse manifested itself in the spread of civilizationism. Making both domestic and foreign policy process more personalized Erdoğan has reinforced ‘personal authoritarianism’ at the expense of the state institutions. Thus their decline led to the ‘Erdoğanization of the Turkish politics’. The declarative pursuit of Turkey to get more independent and autonomous position in the international system resulted in the strategy of development with primarily focus on the bilateral relations with diﬀerent states. Consequently Turkey, previously known as a consistent advocate of regional cooperation and integration, in many respects has become a regionally isolated state.